US-China AI Competition in the Arab Gulf: Diverging Uses of Technological Statecraft on the Regional Level - Rory Miller (12489124) (2025)
In the context of systemic change from a unipolar order to one characterized by multipolarity, artificial intelligence (AI) is viewed by the United States (US) and China not just as a transformational technology with apparently unlimited economic potential. It is also viewed as a central area of competition between these great powers that has the potential to redefine geopolitics in the emerging global order. This article argues that AI in the military sphere should be conceptualized as a tool of “technological statecraft.” This is particularly relevant to the Gulf, where AI has the potential to drive systemic changes in regional security and economic order. For over four decades, the US has been the central pillar of Gulf security doctrine. China, for its part, is the region’s leading trading partner. While the US is looking to use military AI to bind its Gulf allies to its side, China is engaging in technological statecraft to win them away from Washington. This illustrates how the abstract, multifaceted nature of AI has facilitated further interdependencies across defense and economic realms while also broadening the strategic autonomy of Gulf states in the multipolar global order. This also demonstrates how the Gulf states are thinking of AI in terms of navigating great power competition in a multipolar world, preserving their agency and strategic autonomy, and advancing their national interests for economic development through smart strategic positioning. Other Information Published in: Alternatives: Global, Local, Political License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/03043754251377866